The Effectiveness Of The Games Manboka and Numbers Card to Increase The Concept Count Beginning at Child age 4 – 5 Years - Prahesti, Swantyka Ilham; Apriliani, Elina Intan; Dewi, Nufitriani Kartika (Universitas Negeri Semarang, 2018)
The purposes of this research are 1) to determine the outcomeof children’s learning development towards the use of beginning calculation concepts using Manbota game tools; 2) to determine the outcome of the children’s development towards the use of beginning calculation concept using number cards game tools; 3) to determine the differences among the result of the study using Manbota and number cards. The research uses the non equivalent control group design. The T test shows that the average percentage of the experimental group 1 changes from 17.75 into 30.55. Meanwhile, the T test shows that the average percentage of the experimental group 2 changes from 19.65 into 22.25. It can be conclude that: 1) the result of children development in beginning reading and writing concept using the Manbota is proven by the experimental class 1 result; 2) the result of children development in beginning reading and writing concept using the Manbota is proven by the experimental class 2; 3) the difference in learning outcomes of the beginning reading and writing concepts using the game Manbota and card numbers is proven through the results of the smaller experimental group increase compared to the experimental group 1. Keywords : Games, Manbota, numbers card, calculate, children